2005
DOI: 10.1590/s0102-05362005000300026
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa indireta de teores de licopeno em frutos de genótipos de tomateiro via análise colorimétrica

Abstract: O pigmento licopeno (C 40 H 56 ) pertence ao subgrupo dos carotenóides não oxigenados, sendo caracterizado por uma estrutura acíclica e simétrica con-CARVALHO, W.; FONSECA, M.E.N.; SILVA, H.R.; BOITEUX, L.S.; GIORDANO, L.B. Estimativa indireta de teores de licopeno em frutos de genótipos de tomateiro via análise colorimétrica. Horticultura Brasileira, Brasília, v.232 n.3, RESUMOO pigmento vermelho licopeno (C 40 H 56 ) é um carotenóide que acumula em frutos, flores e raízes de algumas espécies vegetais, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 18 publications
2
7
1
10
Order By: Relevance
“…The high r 2 value estimated for the validation sample indicates that the trained network is efficient and has the power of generalization. The prediction efficiency found in this study is higher than that observed by Carvalho et al (2005), r 2 = 0.90% for lycopene prediction, using the colorimetric data of tomatoes. On the other hand, Seroczyńska et al (2006) and Doka et al (2013) found r 2 of 0.92 and 0.96%, respectively, when predicting the β-carotene content using the colorimetric data of pumpkin.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…The high r 2 value estimated for the validation sample indicates that the trained network is efficient and has the power of generalization. The prediction efficiency found in this study is higher than that observed by Carvalho et al (2005), r 2 = 0.90% for lycopene prediction, using the colorimetric data of tomatoes. On the other hand, Seroczyńska et al (2006) and Doka et al (2013) found r 2 of 0.92 and 0.96%, respectively, when predicting the β-carotene content using the colorimetric data of pumpkin.…”
Section: Resultscontrasting
confidence: 86%
“…This analytical approach has been used in tomato (Carvalho et al 2005;Fernandez-Ruiz et al 2010), pumpkin (Seroczyńska et al 2006;Itle and Kabelka 2009;Doka et al 2013), and potato (Lu et al 2001). The indirect estimate of the carotenoid content can reduce the time, labor and financial resources in the evaluation stages.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, lycopene directly interferes in fruit appearance, influencing acceptance of consumers. The tomato external coloration results from pulp and peel pigmentation, which is conditioned by the total concentration of carotenoids, influenced by the relation lycopene/beta-carotene, which gives red color to fruits (Santos Junior et al, 2003;Carvalho et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This is important because the evaluation of the yellow hue (pulp b* and pulp h o ) using a colorimeter is less expensive and easier to carry out. Spectrophotometric methods described in the literature for determination of carotenoids are accurate, but very laborious to evaluate numerous progenies, requiring the use of an excessive amount of reagents and time (Carvalho et al, 2005). In tomato, studies investigating the intensity of correlation between chromaticity and pigment concentrations have shown good correlation between fruit color and lycopene content, the predominant carotenoid in this fruit (D'SOUZA et al, 1992;ARIAS et al, 2000).…”
Section: Methodsmentioning
confidence: 99%